Letter - Lizaso, Jose I. de
012a-0054-001 J.I. de Lizaso Delegate of the Basque Government PRIVATE ADDRESS 75 Gloucester Terrace, Hyde Park London W.2. Tel Paddington 5754 2nd September, 1938. Sir Walter Citrine, K.B.E. The Trades Union Congress, Transport House, Smith Square, S.W.1 Dear Sir Walter Citrine, I want to apologise for not having answered your letter of 3rd August, before; the fact is that it arrived during my absence in Paris, from where I have just returned. It is very good indeed of you to offer to give Mr. Ramon de la Sota some introductions to officials of the American Federation of Labor. These, I know, would be very useful to him. I am looking forward very much to meeting you in the near future, since there have been a number of developments in the Spanish situation which I should like to have the opportunity of discussing with you. Would it be convenient for you to have lunch with me on either Monday or Tuesday of next week? If this is inconvenient, then perhaps you could give me a choice of two dates. Yours sincerely, Jose I. de Lizaso 292/946/12a/54